2011
DOI: 10.1371/journal.pone.0016356
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal Genes for Subcutaneous Fat Thickness in Human and Pig Are Identified by Local Genomic Sequencing and Combined SNP Association Study

Abstract: Obesity represents a major global public health problem that increases the risk for cardiovascular or metabolic disease. The pigs represent an exceptional biomedical model related to energy metabolism and obesity in humans. To pinpoint causal genetic factors for a common form of obesity, we conducted local genomic de novo sequencing, 18.2 Mb, of a porcine QTL region affecting fatness traits, and carried out SNP association studies for backfat thickness and intramuscular fat content in pigs. In order to relate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
56
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(59 citation statements)
references
References 57 publications
1
56
0
1
Order By: Relevance
“…Another association study that combined human and pig data showed that several neuronal genes were associated with subcutaneous fat accumulation, which provides further support for a role of the nervous system on fat metabolism [47]. Another gene, SLC14A2 which is a member of the SLC super family, is mainly expressed in brain [52] and associated with fat thickness in humans and pigs [47]. Since the fat accumulation process probably affects the body structure and movement pattern of an animal, it would be interesting to investigate further how the nervous system influences conformation traits.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…Another association study that combined human and pig data showed that several neuronal genes were associated with subcutaneous fat accumulation, which provides further support for a role of the nervous system on fat metabolism [47]. Another gene, SLC14A2 which is a member of the SLC super family, is mainly expressed in brain [52] and associated with fat thickness in humans and pigs [47]. Since the fat accumulation process probably affects the body structure and movement pattern of an animal, it would be interesting to investigate further how the nervous system influences conformation traits.…”
Section: Discussionmentioning
confidence: 94%
“…For example, some of the candidate genes are expressed in neuronal tissues and are related to the activity of the neuronal system, i.e. SLC14A2 , PPM1G and NGFR [4749]. The role of neuronal genes in the regulation of the metabolism, fat accumulation and body weight gain was investigated in humans and pigs [47, 50, 51].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The adjusted phenotypes were used in the association analyses with the PLINK basic “–assoc” command. To control for population structure and to perform multiple testing, genomic control (GC) followed by FDR was implemented on the empirical P values using the “–gc –adjust” command in PLINK software [28]. As no SNP was significantly associated with the studied traits after GC and FDR, except for LMA, associations were considered significant based on GC corrected P values at a threshold of 0.01, as earlier reported by [28].…”
Section: Methodsmentioning
confidence: 99%